ANALISIS GAYA BAHASA DALAM LIRIK LAGU “AJAIB” OLEH GEMPITA KAJIAN STILISTIKA - Nurjanah, Anisa; Zoni Sulaiman; Zainah Asmaniah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Analysis of Language Style in the Lyrics of the Song "Ajaib" by Gempita Stylistic Studies. This research aims to examine the use of language styles in the lyrics of the song "Ajaib" sung by Gempita through a stylistic approach. The language style contained in the lyrics of this song utilizes various language elements which function to convey messages, emotions and meaning in an effective way to listeners. The analysis was carried out using a qualitative approach, with a focus on identifying and interpreting language styles such as metaphor, personification, repetition and alliteration. The findings from this analysis show that the language style in the lyrics of the song "Ajaib" plays a role in enriching artistic expression, deepening emotional impressions, and creating a strong impact on listeners. Apart from that, the language style used also reflects unique characteristics in conveying messages about magic and extraordinary feelings which are the core of the song's theme. It is hoped that this research will provide deeper insight into the role of linguistic style in popular music works, especially in creating an aesthetic experience for listeners.